Re-Analysis of Neutron Capture on 90,92Zr at s-Process Energies - Ul Abideen, Zain; Khan, Abdul Kabir (The Nucleus, 2025)
The Maxwellian-averaged cross sections (MACS) for the 90,92Zr(n,γ)91,93Zr processes were analyzed within the framework of the Hauser-Feshbach theory, making use of microscopic nuclear inputs. The effects of nuclear level densities and photon strength functions were studied for the mentioned isotopes. A comparison with the experimental data and KADoNiS was conducted at the s-process energies. Good agreement was achieved for both nuclear reactions under study. Finally, making use of the best-fit microscopic nuclear ingredients, we calculated the thermonuclear reaction rates, which show a reduction from the previously reported calculations.